Industrial Multiple-Effect Fractional Condensation under Vacuum for the Recovery of Hop Terpene Fractions in Water - Lorenzo Lamberti; Luisa Boffa; Giorgio Grillo; Stefano Concari; Francesca Cavani; Giancarlo Cravotto (Foods, 2023)
The inflorescences of Humulus lupulus L. are the most valuable ingredient in the brewing industry. Only female cones are used as their bitterness and aroma, much associated with beer, are granted by the production of resins and essential oils, respectively. The traditional brewing process for the extraction of the organic volatiles in hops is called dry hopping. It consists of extended maceration at low temperature after the fermentation phase. New extraction technologies can improve extraction rates and product quality while saving time and money. This article proves that multiple-effect fractional condensation under a vacuum is suitable for flavouring applications and especially for performing dry hopping without contamination risks and reductions in hop amounts. This technique leads to the recovery of aqueous aromatic fractions that are very rich in hop sesquiterpenes and monoterpenes. These suspensions are extremely stable when stored at 5–8 °C and avoid degradation even after several months. This feature is crucial for the marketing of non-alcoholic beverages, where the dilution of essential oils is otherwise problematic.